The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/cancers16071276
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Strategies for the Treatment of Glioblastoma: Current Challenges and Future Perspectives

Ilaria Salvato,
Antonio Marchini

Abstract: Despite decades of research and the best up-to-date treatments, grade 4 Glioblastoma (GBM) remains uniformly fatal with a patient median overall survival of less than 2 years. Recent advances in immunotherapy have reignited interest in utilizing immunological approaches to fight cancer. However, current immunotherapies have so far not met the anticipated expectations, achieving modest results in their journey from bench to bedside for the treatment of GBM. Understanding the intrinsic features of GBM is of cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 362 publications
(344 reference statements)
0
0
0
Order By: Relevance
“…TMZ is typically taken seven days a week for six weeks at a dosage of 75 mg/m 2 during the initial treatment phase. After this, patients undergo six cycles of adjuvant TMZ therapy at a dosage ranging from 150 to 200 mg/m 2 [ 8 ]. Each cycle spans 28 days and includes five days of TMZ administration.…”
Section: Chemotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…TMZ is typically taken seven days a week for six weeks at a dosage of 75 mg/m 2 during the initial treatment phase. After this, patients undergo six cycles of adjuvant TMZ therapy at a dosage ranging from 150 to 200 mg/m 2 [ 8 ]. Each cycle spans 28 days and includes five days of TMZ administration.…”
Section: Chemotherapymentioning
confidence: 99%
“…Additionally, GBMs are heterogeneous, with a lower mutational burden and reduced PD-L1 expression compared to other responsive tumor types. Although ICI treatment on its own has not significantly extended the survival of patients with GBM, upcoming studies should investigate the potential of combining ICI with various other immunotherapies such as CAR-T, oncolytic viruses, vaccines, or with alternative approaches like stereotactic surgery and localized chemotherapy [ 8 ] ( Figure 1 ).…”
Section: Gene and Cell Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, an improved drug distribution could result in increased toxicity, and tumor specificity becomes a more important factor to take into consideration. New trials studying CED in combination with tumor-specific therapeutic agents like nanoparticles or oncolytic viruses are, therefore, of special interest [ 124 ]. Desjardins et al reported the safety of intratumoral injection of the oncolytic polio/rhinovirus recombinant (RVSRIPO) that showed no neurovirulent potential but is specifically targeted to tumor cells and dendritic cells [ 125 ].…”
Section: Can We Ignore the Bbb?mentioning
confidence: 99%